Analisis Minat Menjadi Guru Mahasiswa Pendidikan Ekonomi UNIMED Stambuk 2022 - Meiriza, Mica Siar; Hutagalung, Marshanda; Firmansyah, Deyren; Situmeang, Venus; Annuradi, M. Abdan Syakura (Ikatan Da'i Indonesia, 2024)
The focus of this study is to analyze student interest in the economics education program to become a teacher at UNIMED Stambuk 2022. This study is qualitative research that uses a questionnaire distribution approach. The population of this research is 30 students majoring in economic education in Stambuk 2022. The ability of economic education students to become teachers is very important in determining the quality of education. Several aspects that influence teacher readiness include the role of parents, educational outcomes, peer orientation, and practical teaching experience. However, interest in the teaching process, interpersonal communication skills, and a deep understanding of basic educational material also play a positive role in increasing teacher readiness. The lack of interest of economic education students in teaching economics subjects can be caused by various factors such as challenges in teaching these subjects, lack of awards, and the complexity of the certification process. Evaluation of elements that impact readiness to become a teacher, such as physical and mental abilities, mastery of subject matter, and social abilities, can also help increase teacher interest in economics education students. Motivation and interest play an important role in shaping readiness to become a teacher.